Effect of differentiation on microRNA expression in bovine skeletal muscle satellite cells by deep sequencing. Issue 1 (December 2016) - Zhang, Wei; Sun, Xiao; Tong, Hui; Wang, Ya; Li, Shu; Yan, Yun; Li, Guang
Abstract Background The differentiation of skeletal muscle-derived satellite cells (MDSCs) is important in controlling muscle growth, improving livestock muscle quality, and healing of muscle-related disease. MicroRNAs (miRNAs) are a class of gene expression regulatory factors, which play critical roles in the regulation of muscle cell differentiation. This study aimed to compare the expression profile of miRNAs in MDSC differentiation, and to investigate the miRNAs which are involved in MDSC differentiation. Method Total RNA was extracted from MDSCs at three different stages of differentiation (MDSC-P, MDSC-D1 and MDSC-D3, representing 0, 1 and 3 days after differentiation, respectively), and used to construct small RNA libraries for RNA sequencing (RNA-seq). Results The results showed that in total 617 miRNAs, including 53 novel miRNA candidates, were identified. There were 9 up-expressed, 165 down-expressed, and 15 up-expressed, 145 down-expressed in MDSC-D1 and MDSC-D3, respectively, compared to those in MDSC-P. Also, 17 up-expressed, 55 down-expressed miRNAs were observed in MDSC-D3 compared to those in MDSC-D1. All known miRNAs belong to 237 miRNA gene families. Furthermore, we observed some sequence variants and base edits of the miRNAs. GO and KEGG pathway analysis showed that the majority of target genes regulated by miRNAs were involved in cellular metabolism, pathways in cancer, actin cytoskeleton regulation and the MAPK signaling pathway. Regarding the 53 novel miRNAs, there were 7 up-expressed, 31 down-expressed, and 8 up-expressed, 26 down-expressed in MDSC-D1 and MDSC-D3, respectively, compared to those in MDSC-P. The expression levels of 12 selected miRNA genes detected by RT-qPCR were consistent with those generated by deep sequencing. Conclusions This study confirmed the authenticity of 564 known miRNAs and identified 53 novel miRNAs which were involved in MDSC differentiation. The identification of novel miRNAs has significantly expanded the repertoire of bovine miRNAs and could contribute to advances in understanding muscle development in cattle.